FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK HOTEL DI KABUPATEN/KOTA PROVINSI JAWA TIMUR - Pracelia, Yonanda Annisa; Fazaalloh, Al Muizzuddin (Journal of Development Economic and Social Studies, 2024)
The regencies/cities in the East Java Province are among the regions that possess diverse and significant potential for tourism and local resources or wealth. This research aims to determine the influence of the number of hotels, the number of tourists, the number of hotel rooms, and economic growth on hotel tax revenue in the regencies/cities of East Java Province. In this study, the chosen method is quantitative method with panel data regression analysis. The research results indicate that the Number of Hotels, Number of Hotel Rooms, and Economic Growth have a positive and significant impact on hotel tax revenue in the Districts/Cities of the East Java Province. Meanwhile, the Number of Tourists does not have a effect on hotel tax revenue in the Districts/Cities of the East Java Province.